2016
DOI: 10.1007/s12011-016-0788-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Effect of Zinc Supplementation on Expressed Levels of Peroxisome Proliferator-Activated Receptor Gamma and Glucose Transporter Type 1 Genes in Newborns of Women with Gestational Diabetes Mellitus

Abstract: The current study was designed to determine the beneficial effects of zinc supplementation on expressed levels of peroxisome proliferator-activated receptor gamma (PPAR-γ) and glucose transporter type 1 (GLUT1) genes in newborns of women with gestational diabetes mellitus (GDM). This randomized, double-blind, placebo-controlled clinical trial was performed among 40 women with GDM. Patients were randomly allocated to intake either 233 mg zinc gluconate (containing 30 mg zinc) (n = 20) or a placebo (n = 20) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We observed altered responses of PPAR-γ expression in cell cultures of offspring from overweight and obese mothers compared to cell cultures of newborns of normal weight mothers. These findings support the notion that an obesogenic intrauterine environment promotes changes in the response to metabolic challenges; miR-155 and miR-221 downregulation is associated with CREB, C/EBP, and PPAR-γ upregulation [20,25]. In accordance to this, PBMCs from offspring of obese mothers cultured without stimuli showed overexpression of PPAR-γ compared to those of offspring from normal weight mothers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed altered responses of PPAR-γ expression in cell cultures of offspring from overweight and obese mothers compared to cell cultures of newborns of normal weight mothers. These findings support the notion that an obesogenic intrauterine environment promotes changes in the response to metabolic challenges; miR-155 and miR-221 downregulation is associated with CREB, C/EBP, and PPAR-γ upregulation [20,25]. In accordance to this, PBMCs from offspring of obese mothers cultured without stimuli showed overexpression of PPAR-γ compared to those of offspring from normal weight mothers.…”
Section: Discussionsupporting
confidence: 86%
“…Several metabolic pathways regulated by this nuclear receptor are affected in gestational diabetes, and altered levels of PPAR-γ have been found in fetal and placental tissue in gestational diabetes and other pregnancy disorders [17, 18]. However, information regarding the expression of PPAR-γ, as well as its regulatory mechanisms in neonates and infants, is limited [19, 20]. Because some microRNAs can modulate PPAR-γ expression, they might play a role in shaping of metabolic responses in neonates born to mothers with obesity [10, 21].…”
Section: Introductionmentioning
confidence: 99%
“…PPARs are ligand-activated transcription factors, and PPARγ regulates fatty acid, glucose, and energy homeostasis ( 38 ). Studies have shown that Zn supplementation could increase PPARγ expression ( 39 ), since the PPAR-DNA binding seems to occur through ZnDs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the obesity-related biomarker, peroxisome proliferator-activated receptor-gamma (PPARγ), is a nuclear receptor protein that regulates fatty acid and glucose homeostasis. Zn supplementation may increase PPARγ expression, resulting from the two ZnDs that can bind to DNA ( 16 ).…”
Section: Introductionmentioning
confidence: 99%